George H. Whipple. Premio Nobel en Fisiología y Medicina en 1934. La enfermedad de Whipple, la anemia perniciosa y otras contribuciones a la medicina - Ortíz Hidalgo, Carlos Federico (My University, 2002)
George Hoyot Whipple (1878-1976) fue galardonado con el Premio Nobel en Medicina junto con Minot y Murphy en 1934 por sus estudios sobre la anemia perniciosa. Además, su nombre ha quedado escrito en la enfermedad que describió en 1907 conocida hoy como "Enfermedad de Whipple" o lipodistrofia intestinal. Dio el nombre de talasemia o anemia del Mediterráneo de Cooley e hizo diversas contribuciones a la hematología y a la patología general. Trabajó como patólogo al lado de William Welch en Johns Hopkins en Baltimore y fue Director de la Universidad de Rochester. Murió en 1976 a la edad de 98 años. © Gaceta Medica de México

George Hoyot Whipple (1878-1976) was awarded the Nobel Prize in Physiology and Medicine in 1934, along with Minot and Murphy for their studies in pernicious anemia. Whipple's name has been given to the bacterial disease which he describes in 1907 that we know today as Whipple's disease or intestinal lipodystrophy. He gave the name of thalasemia to the Mediterranean anemia of Cooley, and made diverse contributions to hematology and general pathology. He worked with William Welch in the Department of Pathology at Johns Hopkins Hospital and later became director of the University of Rochester. He died in 1976 at the age of 98.© Gaceta Medica de México
George H. Whipple. Nobel Prize in Physiology or Medicine in 1934. Whipple's disease, pernicious anemia and other contributions to medicine
Keywords: Whipple George Hoyt (1878-1976)